PENDIDIKAN DAN PELATIHAN MITIGASI BENCANA BAGI MASYARAKAT DAN PEMUDA KARANG TARUNA DI DESA PAGERHARJO SAMIGALUH KULONPROGO - Sarwidi Sarwidi; Mutiara Mutiara (UII, 2018)
The process of human development is done to anticipate the various changes that occur, the changes that occur such as advances in science and technology that must always be built and renewed by humans. In addition, the process of changing the world is not always positive, it is a matter of consideration, bahwasannya human development must be arranged to survive and anticipate the extreme changes in the world in the form of disaster. As one of the villages on the slopes of Menoreh Hills, Pagerharjo Village is part of Kulonprogo Regency which has the potential to experience flood and landslide. The presence of students of KKN UII aims to provide education and training on disaster mitigation. Pagerharjo Village is a village that has many natural potential but is vulnerable to disaster. The problem faced is when the community and youth of Karang Taruna are blessed with knowledge and lack of resources to be able to get knowledge about disaster mitigation. Therefore a solution is needed to provide and improve the science of disaster mitigation so that people can be more aware of the hazards of the disaster and can anticipate when the disaster occurs. Disaster mitigation education and training should be developed as a forum to facilitate the community, increasing public awareness pre-disaster symptoms, the community can identify disaster prone areas and increase awareness of the impact of the disaster.